Human bone marrow-derived and umbilical cord-derived mesenchymal stem cells for alleviating neuropathic pain in a spinal cord injury model. Issue 1 (December 2016) - Yousefifard, Mahmoud; Nasirinezhad, Farinaz; Shardi Manaheji, Homa; Janzadeh, Atousa; Hosseini, Mostafa; Keshavarz, Mansoor
Abstract Background Stem cell therapy can be used for alleviating the neuropathic pain induced by spinal cord injuries (SCIs). However, survival and differentiation of stem cells following their transplantation vary depending on the host and intrinsic factors of the cell. Therefore, the present study aimed to determine the effect of stem cells derived from bone marrow (BM-MSC) and umbilical cord (UC-MSC) on neuropathic pain relief. Methods A compression model was used to induce SCI in a rat model. A week after SCI, about 1 million cells were transplanted into the spinal cord. Behavioral tests, including motor function recovery, mechanical allodynia, cold allodynia, mechanical hyperalgesia, and thermal hyperalgesia, were carried out every week for 8 weeks after SCI induction. A single unit recording and histological evaluation were then performed. Results We show that BM-MSC and UC-MSC transplantations led to improving functional recovery, allodynia, and hyperalgesia. No difference was seen between the two cell groups regarding motor recovery and alleviating the allodynia and hyperalgesia. These cells survived in the tissue at least 8 weeks and prevented cavity formation due to SCI. However, survival rate of UC-MSC was significantly higher than BM-MSC. Electrophysiological evaluations showed that transplantation of UC-MSC brings about better results than BM-MSCs in wind up of wide dynamic range neurons. Conclusions The results of the present study show that BM-MSC and UC-MSC transplantations alleviated the symptoms of neuropathic pain and resulted in subsequent motor recovery after SCI. However, survival rate and electrophysiological findings of UC-MSC were significantly better than BM-MSC.